Treatment of sialolithiasis: What has changed? an update of the treatment algorithms and a review of the literature - Koch, Michael; Mantsopoulos, Konstantinos; Müller, Susanna; Sievert, Matti; Iro, Heinrich (Journal of Clinical Medicine, 2022)
Treatment for sialolithiasis has undergone significant changes since the 1990s. Following the development of new minimally invasive and gland-preserving treatment modalities, a 40–50% rate of gland resection was reduced to less than 5%. Extracorporeal shock-wave lithotripsy (ESWL), refinement and extension of methods of transoral duct surgery (TDS), and in particular diagnostic and interventional sialendoscopy (intSE) are substantial parts of the new treatment regimen. It has also become evident that combining the different treatment modalities further increases the effectiveness of therapy, as has been especially evident with the combined endoscopic–transcutaneous approach. In the wake of these remarkable developments, a treatment algorithm was published in 2009 including all the known relevant therapeutic tools. However, new developments have also taken place during the last 10 years. Intraductal shock-wave lithotripsy (ISWL) has led to remarkable improvements thanks to the introduction of new devices, instruments, materials, and techniques, after earlier applications had not been sufficiently effective. Techniques involving combined approaches have been refined and modified. TDS methods have been modified through the introduction of sialendoscopy-assisted TDS in submandibular stones and a retropapillary approach for distal parotid sialolithiasis. Recent trends have revealed a potential for significant changes in therapeutic strategies for both major salivary glands. For the submandibular gland, ISWL has replaced ESWL and TDS to some extent. For parotid stones, ISWL and modifications of TDS have led to reduced use of ESWL and the combined transcutaneous–sialendoscopic approach. To illustrate these changes, we are here providing an updated treatment algorithm, including tried and tested techniques as well as promising new treatment modalities. Prognostic factors (e.g., the size or location of the stones), which are well recognized as having a strong impact on the prognosis, are taken into account and supplemented by additional factors associated with the new applications (e.g., the visibility or accessibility of the stones relative to the anatomy of the duct system).
CRIS-Team Scopus Importer:2022-01-07
Keywords: Combined treatment; Extracorporeal lithotripsy; Intraductal lithotripsy; Salivary gland; Sialendoscopy; Sialolithiasis; Transoral duct surgery; Treatment